METALLURGY OF THE ANCIENT USTRUSHANA IN THE MIDDLE AGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article analyzes some features of ancient and medieval metallurgy of Ustrushana, which is considered a historical and cultural land in Central Asia. Geographically, Ustrushana territory was considered a contact area between the inhabitants of the ancient steppe culture and the representatives of the settled culture. Metal raw materials and products were considered the main support of relations between them. The article compares the results of the physical analysis of the samples taken from the metal melting furnaces and the spectral analysis of the samples taken from the Miq monument. As a result of this comparison, preliminary estimates are presented. Conclusions are made based on the information provided by Arab tourists and preliminary estimates regarding Ustrushana metallurgy.